Proses Penanganan Kasus Kekerasan Seksual Pada Anak Berkebutuhan Khusus di Unit Pelaksana Teknis Daerah Perlindungan Perempuan dan Anak (UPTD PPA) Kota Medan - Annisa Amanda Putri; Fajar Utama Ritonga (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
Children with Special Needs are those with limitations in intellectual, mental, physical, social, or emotional functioning. Individuals with disabilities are at a high risk of experiencing sexual violence due to social isolation, limited sexual education, dependence on others for intimate hygiene, reduced physical defenses, and communication barriers hindering the disclosure of abuse. The implementation of child protection is crucial to ensure that all children are nurtured and raised in a supportive environment that meets their basic rights in terms of physical, psychological, and social needs, enabling them to grow and develop optimally while protecting them from various forms violence. UPTD PPA Kota Medan is one of the organizations providing protection for women and children experiencing violence and discrimination, established by the local government. The aim of this research is to understand the process of handling cases of sexual violence against children with special needs at UPTD PPA Kota Medan. This qualitative descriptive study employs data collection techniques such as in-depth interviews, literature review, and documentation with a triangulation approach. The collected data are qualitatively analyzed by the researcher, and the study concludes with findings drawn from the research results. The research reveals that handling of cases involving children with special needs comprises three stages: the initial stage involving case reporting, case outreach, and case identification; the middle stage involving obtaining informed consent, interviews and screening, as well as victim needs assessment; and the final stage involving the provision of necessary services such as legal assistance, healthcare support, and psychological support.